Body Composition in Various Age Groups Among Individual and Team Sport - Manzoor Ahmad Bhat (JUARA : Jurnal Olahraga, 2021)
The study aimed to compare the Body Composition in Various Age Groups among Individual and Team Sport. A total of one hundred twenty (120) subjects, comprising 60 Individual and 60 Team sport of district Kulgam J&K, further out of 60 individual sports players 20 players were of the age group between 20-25, ( 20 ) players were of the age group between 25- 30 and 20 players were of the age group between 30-35. the same procedure was followed for 60 team sports players. The Subjects were selected by using purposive sampling. The age of the subjects ranged between 20-25, the second group 25-30, and the third group 30-35. To analyze and compare the Body Composition and fat percentage in three different age groups among individual sports and team sports, the Following equipment and test were used: the data related to Fat Percentage was measured by Skinfold Calipers. BMI: it was estimated by Stadiometer and weighing machine. ).the data that was collected after applying standard testing kits were written in separate columns and was cross-checked for all three different age groups. Individual and team sports of district kulgam. Then the analysis of data was carried out by applying various statistical techniques like average., standard deviation and through the application of formula of t-test to find out the significant difference of all selected physical variables I,e BMI and fat percentage in various age groups among individual and team sports players of kulgam district the level of significance as per norm was kept as (p<0.05). the mean and standard deviation of BMI in 20-25 age group individual game players is ( 22.02 ±2.20) respectively, and the mean and standard deviation of BMI in 20-25 age group of team sports players is (18.01 ±1.81), with an average difference of 4.01. ). Hence individual sports players were found with a higher BMI than team sports players under the 20-25 age group. BMI in the 25-30 age group individual game players is (23.09±1.76) respectively, and the mean and standard deviation of BMI in 25-30 age group of team sports players is (20.07±3.36), with an average difference of 3.02. ). Hence under this age group, the individual sports players were found with a higher BMI than team sports groups. The mean and standard deviation of BMI in 30-35 age group individual game players is (19.30±2.07) respectively, and the mean and standard deviation of BMI in 30-35 age group of team sports players is (22.17 ±3.47), with an average difference of 2.87. Hence, team sports players were found with a higher BMI under the age group than individual sports players. The mean and standard deviation of fat percentage in 20-25 age group individual game players is (11.09±4.83) respectively, and the mean and standard deviation of fat percentage in 20-25 age group of team sports players is (9.02±4.18), with an average difference of 2.17.).Hence under this age group, individual sports players were found fatty as compared to team sports players. The mean and standard deviation of fat percentage in 25-30 age group individual game players is (10.01±3.53) respectively, and the mean and standard deviation of BMI in 25-30 age group of team sports players is (14.04±7.48), with an average difference of 4.13. ). Hence under this age group, team sports players were found fatty as compared to individual sports players. The mean and standard deviation of BMI in 30-35 age group individual game players is (14.08±2.81) respectively, and the mean and standard deviation of fat percentage in 30-35 age group of team sports players is (18.01±5.64), with an average difference of 3.64. Hence under this age group, team sports players were found fatty as compared to individual sports players